Efficiency of Use of Architectural Monuments of Namangan Region (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, the author tried to study the directions and characteristics of the use of architectural monuments in Namangan region for modern purposes, as well as the development processes of ancient architecture in the area of architectural monuments currently used for religious and other purposes, to determine its sources and specific aspects.